1996
DOI: 10.1002/(sici)1097-0290(19960805)51:3<349::aid-bit10>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of trichloroethylene degradation using soluble methane monooxygenase ofMethylosinus trichosporium OB3b expressed in recombinant bacteria

Abstract: By complementing cell-free extracts of fseudomonas putida Fl/pSMM020 with purified soluble methane monooxygenase (sMMO) components of Methylosinus trichosporium OB3b, the low cloned-gene sMMO activity in the recombinant strain was found to be due to incomplete activity of the hydroxylase component. To address this incomplete activity, additional sMMO-expressing strains were formed by transferring mmo-containing pSMM020 and pSMM050 into various bacterial species including pseudomonads and a-2 subdivision strain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…sMMO can be expressed at high levels in heterologous methanotrophs (24,25) and at very low levels in a few other hosts (28,29), but to date, sMMO has not been functionally expressed in E. coli. This limitation has hindered research on this important enzyme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…sMMO can be expressed at high levels in heterologous methanotrophs (24,25) and at very low levels in a few other hosts (28,29), but to date, sMMO has not been functionally expressed in E. coli. This limitation has hindered research on this important enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…sMMO can be expressed in methanotrophs that normally lack sMMO (24,25), which has allowed site-directed mutagenesis (26), but the system has limitations; e.g., the particulate methane MO (pMMO) is also present, and the system is under complex regulatory control (27). sMMO can also be ex-pressed, albeit with very low activity, in Pseudomonas (28) and Rhizobium (29). In the case of sBMO, genetic work has been enabled via homologous recombination in the natural host (Thauera butanivorans) (22), but this approach has some limitations similar to those of the homologous sMMO expression systems; e.g., it requires a gaseous inducer.…”
mentioning
confidence: 99%
“…Previous studies found that this component was inactive when expressed in Escherichia coli (50). The first reports of expression of the genes encoding the sMMO gene cluster of M. trichosporium in a heterologous host were by Wood and colleagues, who demonstrated the degradation of trichloroethylene by sMMO expressed in Pseudomonas putida, Agrobacterium tumefaciens, and Rhizobium meliloti (19,20). We subsequently described a homologous expression system for the wild-type sMMO hydroxylase, in which recombinant (wild-type) sMMO genes were expressed, yielding highly active sMMO in a derivative of M. trichosporium known as mutant F (26).…”
mentioning
confidence: 99%
“…Mutagenesis of the hydroxylase component of sMMO requires the use of an especially developed expression system because attempts to date to obtain expression of active hydroxylase in E. coli have been unsuccessful (44). Expression of active sMMO has been reported to occur in various heterologous systems (16,17,24) as well as the homologous system used here. The previous work that we performed using the homologous expression system for sMMO, which enabled the first mutagenesis of the active site of the enzyme (38), utilized a homologous expression host (M. trichosporium mutant F [26]) from which only part of the mmoX gene was deleted, thus limiting the region of the hydroxylase that could be mutagenized.…”
Section: Discussionmentioning
confidence: 99%